Pengembangan Teknologi ERP Untuk Modul Accounting Management Pada Anzon Toyota Sampit Berbasis Web - Siti Nur Hasanah; Lukman Bachtiar (Journal of Computer System and Informatics (JoSYC), 2020)
Internet technology is growing rapidly nowadays. Apart from providing information, the use of internet technology also leads to online transaction activities. The use of web-based online transactions has been implemented in various fields in the business world. The ease of accessing the internet at this time illustrates how useful and beneficial the internet is. This statement is made clear by the number of programmers who make web-based systems, programs, games, for example online sales systems, education systems, social networks and others. To create a web-based trading business system itself is an action to follow the development of existing technology, besides that this web-based system can be continuously updated, especially by using PHP and MySQL database processing can be controlled. This is clearly very helpful and profitable for business people. Including services such as ordering a car service slot online. PT. Anzon AutoPlaza Sampit is an authorized dealer for marketing Toyota cars after PT. Astra Internasional and PT. Source of the Equator. The field that this company is engaged in is in the field of sales (Marketing) specifically for the Toyota brand. In addition to sales, this company also provides service services, as well as special spare parts for Toyota cars. The facilities provided are sales outlets, authorized Toyota repair shops and car spare parts sales. Accounting is a process that begins with recording, classifying, processing, presenting data, and recording transactions related to finance so that information can be used by someone who is an expert in their field and becomes material for making decisions.